THE EFFECT OF MARKETING MIX ON INTERESTS AND DECISION OF TOURIST IN CHOOSING RELIGIOUS TOURISM - Devi Ayuni; Mailani Hamdani; Irmawaty Irmawaty (JELAJAH: Journal of Tourism and Hospitality, 2019)
This study is aimed to examine and analyze the effect of marketing mix on the interest of tourists in choosing religious tourism as well as to review and analyze the dominant marketing mix take effect on the interest of tourists in choosing religious tourism. The data analysis is using Partial Least Square (PLS) method and Smart PLS tools. The result of this study show that marketing mix significantly take effect on the interest of visiting. This also show that the marketing mix of religious tourism product offered can shape the interest of visiting. In addition, the marketing mix has also a significant effect on the visiting decision. This indicates that the marketing mix of religious tourism product offered can form the visiting decision and the visiting interest significantly take effect on the decision to visit. It shows that the tourists' visiting interest can shape a visit decision